VD_FINDINFO Arrêt / 2009 / 321 vom 5. Juni 2009 - VD Tribunal cantonal (2009)
PRESTATION COMPLÉMENTAIRE, PENSIONNAIRE D'UN ÉTABLISSEMENT, DOMICILE | 3b LPC, 2a LVPC, 22 LAPRAMS, 23 LAPRAMS, 28 RLAPRAMS